2016
DOI: 10.1186/s12877-016-0353-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of stable and unstable patterns of subjective cognitive decline – results from the Leipzig Longitudinal Study of the Aged (LEILA75+)

Abstract: BackgroundSubjective cognitive decline (SCD), i.e., the self-perceived feeling of worsening cognitive function, may be the first notable syndrome of preclinical Alzheimer’s disease and other dementias. However, not all individuals with SCD progress. Stability of SCD, i.e., repeated reports of SCD, could contribute to identify individuals at risk, as stable SCD may more likely reflect the continuous neurodegenerative process of Alzheimer’s and other dementias.MethodsCox regression analyses were used to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
0
24
1
1
Order By: Relevance
“…The findings are consistent with recent literature on the relevance of longitudinal assessment of SCD in identifying individuals at high risk of neurocognitive disorders. In particular, the presence of Persistent SCD over time has consistently been highlighted in recent literature as a key predictor of incident neurocognitive disorders [ 44 46 ]. This finding is understandable, given that neurocognitive disorders are conceptualized as progressive neurodegenerative diseases, and hence in the face of progressive neuropathological processes, individuals are more likely to experience persistent rather than transient symptoms of SCD [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings are consistent with recent literature on the relevance of longitudinal assessment of SCD in identifying individuals at high risk of neurocognitive disorders. In particular, the presence of Persistent SCD over time has consistently been highlighted in recent literature as a key predictor of incident neurocognitive disorders [ 44 46 ]. This finding is understandable, given that neurocognitive disorders are conceptualized as progressive neurodegenerative diseases, and hence in the face of progressive neuropathological processes, individuals are more likely to experience persistent rather than transient symptoms of SCD [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is understandable, given that neurocognitive disorders are conceptualized as progressive neurodegenerative diseases, and hence in the face of progressive neuropathological processes, individuals are more likely to experience persistent rather than transient symptoms of SCD [ 43 , 44 ]. In contrast, the evidence on the relevance of Intermittent SCD was more conflicting in the literature, with one study showing no association with incident neurocognitive disorders [ 44 ], another study showing significant association only with informant-reports and not self-reports of SCD [ 45 ], while yet another study showing significant association but in the negative direction (i.e., presence of Intermittent SCD was associated with a lower risk of neurocognitive disorders) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies of the long-term prognosis of SCD have identified a variety of potential clinical trajectories, including symptom remittance. Those with persistent symptoms reported over a number of time points appear to be at greater risk of progression to MCI or dementia, whilst those who intermittently report cognitive symptoms are not at increased risk, compared to people who have never reported cognitive symptoms [18]. Clearly, in the instances of SCD and MCI, diagnostic status is often a dynamic concept.…”
Section: Discussionmentioning
confidence: 99%